Cathepsin B is a potential therapeutic target for coronavirus disease 2019 patients with lung adenocarcinoma. (1st February 2022) - Ding, Xiaoyan; Ye, Nan; Qiu, Minyue; Guo, Hongxia; Li, Junjie; Zhou, Xiaoyang; Yang, Maocheng; Xi, Jing; Liang, Yongjie; Gong, Yuanxin; Li, Jintao
Abstract: Coronavirus disease 2019 (COVID-19) was declared a serious global public health emergency. Hospitalization and mortality rates of lung cancer patients diagnosed with COVID-19 are higher than those of patients presenting with other cancers. However, the reasons for the outcomes being disproportionately severe in lung adenocarcinoma (LUAD) patients with COVID-19 remain elusive. The present study aimed to identify the possible causes for disproportionately severe COVID-19 outcomes in LUAD patients and determine a therapeutic target for COVID-19 patients with LUAD. We used publicly available data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and various bioinformatics tools to identify and analyze the genes implicated in SARS-CoV-2 infection in LUAD patients. Upregulation of the SARS-CoV-2 infection-related molecules dipeptidyl peptidase 4, basigin, cathepsin B (CTSB), methylenetetrahydrofolate dehydrogenase, and peptidylprolyl isomerase B rather than angiotensin-converting enzyme 2 may explain the relatively high susceptibility of LUAD patients to SARS-CoV-2 infection. CTSB was highly expressed in the LUAD tissues after SARS-CoV-2 infection, and its expression was positively correlated with immune cell infiltration and proinflammatory cytokine expression. These findings suggest that CTSB plays a vital role in the hyperinflammatory response in COVID-19 patients with LUAD and is a promising target for the development of a novel drug therapy for COVID-19 patients. Highlights: DPP4, BSG, CTSB, MTHFD1 but not ACE2 explain SARS-CoV-2 susceptibility in LUAD. CTSB expression correlated with immunocyte infiltration in LUAD patients. CTSB expression correlated with hyperinflammatory response in COVID-19 patients. CTSB upregulation associated with poor prognosis in LUAD patients. CTSB is promising drug development target for COVID-19 patients with LUAD.